Insights in the Effect of Fluctuating Female Hormones on Injury Risk—Challenge and Chance - Legerlotz, Kirsten; Nobis, Tina (Frontiers in Physiology, 2022)
It is time to take on the challenge of investigating the complex effect of fluctuating female hormones on injury risk as this offers a chance to improve female athletes’ health and performance. During the recent decade the body of knowledge on female hormones and injury risk has largely been increased. New insights have been offered regarding the association of certain phases of the menstrual cycle and injury prevalence as well as regarding relationships between hormone levels and musculoskeletal changes such as e.g. ligamentous stiffness and knee laxity. However, current research often follows the theme of a causal relationship between estrogen-levels and musculoskeletal function or injury and thus – one might argue – further enhances a rather simplistic approach, instead of uncovering complex relationships which could help in establishing more nuanced ways of preventing female injuries. To uncover real effects and to truly understand the physiological responses we suggest to reflect on potential bias regarding research questions and current approaches. It may enhance future studies to apply a more nuanced approach to causation, to include multidimensional perspectives and to implement an interdisciplinary methodology.